PENGARUH PENERAPAN LEMBAR KEGIATAN SISWA BERMUATAN KECERDASAN KOMPREHENSIF MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERHADAP PENINGKATAN KOMPETENSI FISIKA SISWA KELAS X SMAN 4 PADANG - Suliati Suliati; Mahrizal Mahrizal; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2016)
The Competence has not been achieved optimally because of learning activity has not been dominated by students, learning model used was not able yet to guide students in scientific study. Learning sources used by the students were still dominated by materials which improve the competence of knowledge. The purpose of this research was to investigate the effect of applying students worksheet contains comprehensive intelligence with inquiry learning model towards the improvement of competence of physics students grade X at SMAN 4 Padang. It was a Quasi-experimental research with Randomized Control Group Only Design. The population were the students grade X at SMAN 4 Padang who were registered in the Academic Year of 2015/2016, and the sample was taken by using Purposive Sampling technique. The instruments were written test for competence of knowledge, observation sheet for competence of spiritual and social, performance assessment rubric for competence of skill. The competence of knowledge data were analyzed by using t-test, product moment correlation and regression analysis. Competence of spiritual, social and skills were analyzed by using t-test. The results of data analysis showed significant differences between both of sample classes. Differences in competence of knowledge were 63.96% influenced by the implementation of a worksheet contains comprehensive intelligence and the remaining were 36.04% influenced by other factors. It can be concluded that there is a significant impact on the implementation of a worksheet contains comprehensive intelligence  by using inquiry learning model towards the improvement of competence of Physics students grade X at SMAN 4 Padang